A 3.3-W passive Q-switched 2-µm laser with a MoS2-based saturable absorber. Issue 3 (March 2019) - Li, Guoxing; Yang, Xining; Zhou, Long
Abstract: Using a new MoS2 -based nanosheets as a saturable absorber (SA), a passively Q-switched (PQS) Tm, Ho:YAP laser at 2000.4 nm was proved in the paper. Under PQS mode, an average output power of over 3 W and per pulse energy of over 23 μJ were obtained in the experiment. Also, the beam quality factors were less than 1.1 in PQS mode.